A survey of students’ English proficiency and their needs toward learning outcomes at vocational colleges - Anhar Anhar; Sofyan A. Gani; Asnawi Muslem (Universitas Syiah Kuala, 2021)
This research was conducted to investigate students’ English proficiency and their needs toward English learning outcomes. This research was based on a qualitative research design. The data were collected from 80 students who received an English proficiency test and eight students who participated in an interview session. The interview dealt with their needs and problems in communication skills in English. The result shows that there was no student who got excellent English proficiency level, eight students (10%) reached good category, 46 students (58%) achieved satisfactory category, 21 students (26%) were in poor category, and five students (6%) were in very poor category. In addition, all students need English for communication in their future profession. Finally, the results of the interview also show that industrial engineering students preparing to work in manufacturing various marble products face a serious problem in marketing their products to the consumers. In addition, the students majoring in tourism destination area considered that they have to communicate in English to support their job in providing services to tourists speaking different languages. Therefore, it can be concluded that vocational school students need transactional English in a specific field because they are being prepared to work in enterprises or to be entrepreneurs.